Different Words, Same Song: Advice for Substantively Interpreting Duration Models. Issue 4 (October 2019) - Jones, Benjamin T.; Metzger, Shawna K.
ABSTRACT: The use of duration models in political science continues to grow, more than a decade after Box-Steffensmeier and Jones (2004 ). However, several common misconceptions about the models still persist. To improve scholars' use and interpretation of duration models, we point out that they are a type of regression model and therefore follow the same rules as other more commonly used regression models. In this article, we present four maxims as guidelines. We survey the various duration model interpretation strategies and group them into four categories, which is an important organizational exercise that does not appear elsewhere. We then discuss the strengths and weaknesses of these strategies, noting that all are correct from a technical perspective. However, some strategies make more sense than others for nontechnical reasons, which ultimately informs best practices.